Beneficial root endophytic fungus Piriformospora indica inhibits the infection of Blackeye cowpea mosaic virus in yard long bean with enhanced growth promotion - Chandran, K.; Sreeja, S. J.; Johnson, Joy Michal (Journal of Tropical Agriculture, 2021)
Viral diseases are the major constraints in production and yield of yard long bean (vegetable cowpea), of which, Blackeye cowpea mosaic virus (BlCMV), a Potyvirus has been identified as a major threat. Management of diseases caused by plant viruses are very difficult but the use of beneficial root endophytes like Piriformospora indica is gaining importance in recent years for plant disease control. The present study was undertaken to utilize the potential of P. indica for the management of blackeye cowpea mosaic disease of yard long bean caused by BlCMV. The co-cultivation of P. indica with yard long bean and Chenopodium amaranticolor, the systemic and local lesion hosts of BlCMV respectively, was standardized. The seedlings of Chenopodium colonized with P. indica significantly reduced the number of local lesions produced by BlCMV over non-colonized plants. Yard long bean roots colonized with the endophytic fungus, P. indica significantly delayed the symptom development and also reduced vulnerability index to 70 per cent over the non-colonized plants with enhanced shoot and root biomass. This showed that P. indica could be used for managing viral diseases in crop plants with enhanced biomass to produce safe-to-eat farm produce.